2021
DOI: 10.1017/gmh.2021.18
|View full text |Cite|
|
Sign up to set email alerts
|

Psychosocial burden of neglected tropical diseases in eastern Colombia: an explorative qualitative study in persons affected by leprosy, cutaneous leishmaniasis and Chagas disease

Abstract: Background Leprosy, cutaneous leishmaniasis (CL) and Chagas disease (CD) are neglected tropical diseases (NTDs) with a high psychosocial burden in Norte de Santander and Arauca in Colombia. This study provides insights into affected persons' feelings, perceptions and experiences to better understand the nature of this burden. Methods In 2018, 34 leprosy, CD and CL patients participated in four focus groups discussing the influence of the disease on mental well-being, social participation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
15
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 27 publications
0
15
0
2
Order By: Relevance
“…An investigation carried out in Colombia with people affected by leprosy found that the psychosocial burden suffered is due to the stigma experienced, and can impact social participation and professional life. 27 Moreover, in another study conducted in Indonesia and Ghana, it was shown that people with leprosy perceived stigmatization by health care workers, the community, and the labor market. 28 This is corroborated by a study in Nepal which found that depression and a lower state of mental well-being than in the general population is associated with disabilities and the stigma suffered by people affected by leprosy.…”
Section: Discussionmentioning
confidence: 99%
“…An investigation carried out in Colombia with people affected by leprosy found that the psychosocial burden suffered is due to the stigma experienced, and can impact social participation and professional life. 27 Moreover, in another study conducted in Indonesia and Ghana, it was shown that people with leprosy perceived stigmatization by health care workers, the community, and the labor market. 28 This is corroborated by a study in Nepal which found that depression and a lower state of mental well-being than in the general population is associated with disabilities and the stigma suffered by people affected by leprosy.…”
Section: Discussionmentioning
confidence: 99%
“…The main outcomes identified in the studies were leprosy, relapse, nerve function impairment, leprosy reactions and physical disabilities. The mean times and outcomes are key elements of discussion for the prevention and control of leprosy [4,39,40,43].…”
Section: Discussionmentioning
confidence: 99%
“…The etiologic agent is Mycobacterium leprae, an obligate intracellular bacterium with an affinity for the peripheral nervous system [3]. In general, people affected by the disease suffer social and psychological repercussions due to deformities and physical disabilities caused by the disease's progression [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…CL leads to reduced Health Related Quality of Life (HRQL) as a result of social and self-stigma, as has been established in the Asian and Mediterranean contexts [ 5 ]. In contrast, the few studies that assessed HRQL of CL patients in northern South America found no evidence for stigmatization [ 6 , 7 ]. CL patients reported reduced self-esteem in the Ecuadorian subtropical Pacific in 1994 but no follow up was done [ 8 ].…”
Section: Introductionmentioning
confidence: 99%